2015
DOI: 10.1093/hmg/ddv051
|View full text |Cite
|
Sign up to set email alerts
|

Population variation in total genetic risk of Hirschsprung disease from common RET, SEMA3 and NRG1 susceptibility polymorphisms

Abstract: The risk of Hirschsprung disease (HSCR) is ∼15/100 000 live births per newborn but has been reported to show significant inter-individual variation from the effects of seven common susceptibility alleles at the RET, SEMA3 and NRG1 loci. We show, by analyses of these variants in 997 samples from 376 HSCR families of European ancestry, that significant genetic risk can only be detected at RET (rs2435357 and rs2506030) and at SEMA3 (rs11766001), but not at NRG1. RET rs2435357 also showed significant frequency dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(99 citation statements)
references
References 18 publications
4
94
1
Order By: Relevance
“…A major remaining question is how widespread human susceptibility from common enhancer variants, a defining feature of all complex diseases, is converted to clinical disease (Kapoor et al, 2015). The hypotheses include stochastic effects on gene expression, additional variants in other genes dysregulating other GRNs, and environmental effects on gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major remaining question is how widespread human susceptibility from common enhancer variants, a defining feature of all complex diseases, is converted to clinical disease (Kapoor et al, 2015). The hypotheses include stochastic effects on gene expression, additional variants in other genes dysregulating other GRNs, and environmental effects on gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, the most frequent coding mutations occur in RET , encoding a receptor tyrosine kinase (Emison et al, 2010; Emison et al, 2005). Surprisingly, significantly greater risk to the more common, isolated, non-syndromic HSCR arises from three polymorphic, low-penetrance non-coding variants at RET (rs2435357, rs2506030) and SEMA3C/D (rs11766001), in patients of European ancestry (Kapoor et al, 2015). Of these, we have shown that the RET intronic variant rs2435357 has high (~24%) allele frequency, disrupts SOX10 binding to a fetal gut enhancer (CRE: RET+3), reduces RET expression and increases Hirschsprung disease (HSCR) risk 4-fold (Emison et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] The reason for the incomplete migration and development of ganglion cells is as yet not fully understood. Early estimates were that genetic variations could be identified in at least 12% of HSCR cases, which is higher than the expected in the normal population.…”
Section: Genetic Associations Of Hscrmentioning
confidence: 99%
“…The RET intronic SNP rs2435357 has been shown to demonstrate significant frequency differences by affecting RET transcription regulation affecting sex, segment length of aganglionosis, and family recurrence. 18 Mutations affecting the coding of RET mRNA are less common overall and appear more frequently in cases of extended aganglionosis (eg, TCA).…”
Section: Genetic Associations Of Hscrmentioning
confidence: 99%
“…The 3 common polymorphisms were identified in genome-wide association study of HSCR patients of European ancestry and replicated independently [35, 36] The prevalence of each of the variables listed was compared between patients with and without proximal IND-SH using Welch Two Sample T-test, Fisher’s Exact test, or Permutation Chi-Squared test.…”
Section: Methodsmentioning
confidence: 99%